Oxygen and carbon stable isotopes in coast redwood tree rings respond to spring and summer climate signals. Issue 4 (24th October 2013) - Johnstone, James A.; Roden, John S.; Dawson, Todd E.
Abstract [1] Interannual variability in the oxygen and carbon isotope composition of tree ring cellulose was investigated in coast redwood (Sequoia sempervirens) from three sites in coastal Northern California. Middle and late wood samples from annual tree rings were compared to regional climate indices and gridded ocean‐atmosphere fields for the years 1952–2003. The strongest climate‐isotope relationship (r = 0.72) was found with summer (June–September) daily maximum temperature and middle wood δ13, which also responds positively to coastal sea surface temperature and negatively to summer low cloud frequency. Late wood δ18O reflects a balance between 18O‐enriched summer fog drip and depleted summer rainwater, while a combined analysis of late wood δ18O and δ13C revealed sensitivity to the sign of summer precipitation anomalies. Empirical orthogonal function analysis of regional summer climate indices and coast redwood stable isotopes identified multivariate isotopic responses to summer fog and drought that correspond to atmospheric circulation anomalies over the NE Pacific and NW U.S. The presence of regional climate signals in coast redwood stable isotope composition, consistent with known mechanistic processes and prior studies, offers the potential for high‐resolution paleoclimate reconstructions of the California current system from this long‐lived tree species.